Association Between Enhanced Hydration Therapy and Improved Prognosis in Patients With Acute Ischemic Stroke Who Were Treated With Thrombolytics: A Preliminary Study - Leng Chieh Lin; Chen-June Seak; Yen Chu Huang; Yuan Hsiung Tsai; Jen Tsung Yang; Kai-Hsiang Wu; Chia-Peng Chang; Yen Yun Tsai (Emergency Medicine International)
Conclusion: Enhanced hydration therapy can improve outcomes in patients with stroke who had an elevated BCR and who received rt-PA treatment. Further, it is not associated with significant complications.